SURFACE-LEVEL ERRORS IN EFL WRITING: A TAXONOMIC STUDY OF JUNIOR HIGH SCHOOL STUDENTS DESCRIPTIVE TEXTS IN GRADE IX SMP NEGRI 23 MEDAN - Christina N Saragi; Dewi P Silalahi; Devi M Saragi (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2025)
This study examines grammatical errors in descriptive writing among ninth-grade students at SMP Negeri 23 Medan, focusing on their challenges in learning English as a Foreign Language (EFL). This research applies the Surface Strategy Taxonomy framework by Dulay, Burt, and Krashen (1982) to classify students' grammatical errors into four categories: omission, addition, misformation, and misordering. Utilizing a qualitative descriptive approach, the study integrates numerical data to highlight the prevalence of each error type. Writing samples from 15 randomly selected students were examined to identify common patterns and recurring linguistic difficulties. The results indicate that misformation errors are the most frequent (36.1%), followed by omission (28.8%), addition (23%), and misordering (12%).These results emphasize the importance of structured grammar instruction and corrective feedback in enhancing students’ writing skills. The study offers practical recommendations for teachers to refine their instructional methods and support students in developing greater accuracy in written English.